Techniques For Harvesting Forest Honey (Apis dorsata) In Pelawan Forest, Central Bangka District, Indonesia - Evahelda Evahelda; Rufti Puji Astuti; Dian Fery Ramdani; Elakenia Novsa Dioca; Nabila Ayu Wirani (Journal of Global Sustainable Agriculture, 2024)
Forest honey harvest and post-harvest activities in Namang Village still apply traditional methods, namely based on local wisdom carried out by the local community. The research was conducted with the aim of describing harvest and post-harvest activities of forest honey in the Pelawan Forest Biodiversity Park, Namang Village, Central Bangka Regency. The research was carried out in the Pelawan Forest Biodiversity Park, Namang Village, Central Bangka Regency using the case study method. The research location was determined using purposive sampling and respondents were interviewed using a questionnaire. Based on the research results, it is known that the forest honey harvesting activities carried out in Namang Village include characteristics of ready-to-harvest honey, scavenging using a pusung, and nest cutting/harvesting carried out using the circumcision technique. Next, post-harvest activities are carried out which consist of transportation using ropes, jerry cans and motorized vehicles, pressing activities carried out manually, filtering carried out using traditional techniques, and packaging stages.